Non-invasive Glucometer using Acetone Gas Sensor for Low Income Earners’ Diabetes Monitoring - Ajibola, Taiye Mary; Ibitoye, Morufu Olusola; Ahmed, Yusuf Kola; Jimoh, Zainab Gbemisola (ELEKTRIKA- Journal of Electrical Engineering, 2022)
A glucometer is an important device used to monitor blood glucose level of diabetes patients to prevent degenerated health conditions. The conventional glucometers are characterized by piercing of the sample site for patients’ testing. The invasive nature of these glucometers is painful to the patients and some patients are also scared at the sight of blood. To promote glucometer acceptance among patients, it is important to develop a non-invasive glucometer using acetone gas sensor with “exhaled breath” collected non-invasively as the sample for the glucometer. After the device development, exhaled breath sample of twenty subjects with age range of 20 to 55 years from a University were taken using the developed acetone sensor device. Prior to the exhaled breath sample collection, the blood glucose levels of the volunteered subjects were also determined using the conventional and proprietary invasive clinical method. To infer whether there is significant different between the mean of the results obtained from the conventional and the exhaled breath method, a t-test was carried out on the results and P values of 0.9860 and 0.9306 were obtained for fasting blood sugar and random blood sugar respectively, indicating no significant differences in the results obtained from the developed device when compared with the proprietary device. Hence, non-invasive glucometer using acetone gas sensor can be used to promote inexpensive personalized diabetes monitoring without inflicting pain on the patients. Promotion of this device could also reduce the expenses incurred on lancet and test strips, thus, making it suitable for low income earners.